ANALISIS MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA DI SEKRETARIAT DAERAH MAMBERAMO TENGAH - Pandapotan Pangaribuan, Sahat; Tebay, Vince; Sapioper, Hiskia C.M. (Universitas Cenderawasih, 2025)
This study aims to analyze Human Resources management in improving apparatus performance at the Central Mamberamo Regional Secretariat, identify inhibiting factors in the utilization of state apparatus, and formulate efforts to overcome these obstacles. The urgency of this research lies in the importance of optimizing human resource management to improve the effectiveness of public services in disadvantaged areas. The research method is descriptive qualitative with the study location in Central Mamberamo Regency. Research instruments included semi-structured interview guidelines, a voice recorder and camera, as well as a field notebook as a reflection of the researcher while in the field. The technique of determining informants uses a purposive snowball approach, starting from key informants of policy implementers to devices and personnel within the Regional Secretariat. Data were collected through in-depth interviews, active observation, Focus Group Discussions, documentation, and literature studies; then analyzed with the Miles & Huberman interactive model through data reduction, presentation of data in narrative, and verification of findings. The results showed that the development of the quality of HR apparatus was carried out through four main stages: planning based on competency needs and diversification of funding sources, organizing with the formation of special HR units and sharpening tupoksi and SOPs, implementing on-the-job training, workshops, and compulsory training supported by top leadership commitment and Kirkpatrick model evaluation, and integrated supervision mechanisms in the form of periodic performance audits and formal monitoring protocols strengthened by cross-sector partnerships. Obstacles include budget constraints, the absence of internal regulations, suboptimal inter-section coordination, and administrative overload. Efforts to overcome obstacles include revising regulations and job descriptions, forming cross-functional teams with clear budgets, formalizing monitoring protocols, and implementing a continuous feedback system through the Learning Management System and external partnerships.